2003
DOI: 10.1007/s00415-003-1055-7
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic neuropathy in patients with "Latent Autoimmune Diabetes of the Adults" (LADA) compared with patients with type 1 and type 2 diabetes

Abstract: LADA patients had fewer features of diabetic neuropathy than type 2 diabetes patients in the early stages of disease, thus being more similar to classical type 1 diabetes patients who normally develop diabetic neuropathy rather late.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
20
0
2
Order By: Relevance
“…The frequency of retinopathy and nephropathy in LADA is similar to that in type 2 diabetes; neuropathy appears to be uncommon initially but increases with duration of disease [51]. The frequency of retinopathy (51%), nephropathy (microalbuminuria) (27%) and neuropathy (29%) was similar in LADA patients and patients with type 1 diabetes diagnosed for more than 10 years; type 1 diabetic patients had significantly more retinopathy (76%) but less neuropathy (13%) [50].…”
Section: Microvascularmentioning
confidence: 68%
“…The frequency of retinopathy and nephropathy in LADA is similar to that in type 2 diabetes; neuropathy appears to be uncommon initially but increases with duration of disease [51]. The frequency of retinopathy (51%), nephropathy (microalbuminuria) (27%) and neuropathy (29%) was similar in LADA patients and patients with type 1 diabetes diagnosed for more than 10 years; type 1 diabetic patients had significantly more retinopathy (76%) but less neuropathy (13%) [50].…”
Section: Microvascularmentioning
confidence: 68%
“…However, comparative studies are limited in humans (Baum et al, 2003;Isomaa et al, 1999;Lohmann et al, 2001). With the largest sample size to date, this study cross-sectional surveyed 1635 patients with LADA or T2DM who were categorized into 3 duration groups.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DPN did not differ between the two groups (29% vs. 27%). By comparison, in a study comprising 14 patients with LADA and 14 with T2DM, Baum et al (2003) demonstrated that electrophysiological parameters showed a trend toward better outcomes in LADA than in T2DM. However, these studies were compromised by small sample sizes.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In an epidemiological study the risk of painful neuropathy in type 2 diabetes was reported to be double that found in type 1 (Abbott et al, ) . Other studies have also demonstrated a higher prevalence of neuropathy in those with diabetes type 2 (Baum et al, ; Kästenbauer et al, ; Ziegler et al, ) including more depletion of intraepidermal nerve fibers in asymptomatic subjects (Ragé et al, ) . In another epidemiological study of patients with adult diabetes and microvascular complications, occurrence of peripheral neuropathy did not differ between those with diabetes type 1 and type 2 (Happich et al, ) .…”
Section: Discussionmentioning
confidence: 91%